Atmospheres: Feeling Architecture by Emotions - Elisabetta Canepa; Valter Scelsi; Anna Fassio; Laura Avanzino; Giovanna Lagravinese; Carlo Chiorri (Ambiances)
What is architectural atmosphere? To answer this question, we propose a paradox: a precise definition of the inherently vague and ambiguous concept of atmosphere that satisfies, as so far as possible, scientific criteria and methodology. We suggest that the term atmosphere, understood in an architectural context, defines a state of resonance and identification (sensorimotor, emotive, and cognitive) between an individual and their surrounding built space. Human beings can empathise with inanimate rooms when they interiorly establish an embodied simulation of certain architectural features. Thus, atmospheres might be determined, mapped, and measured through quantitative methods tracing emotional, cognitive, and neurophysiological responses of individuals to spatial conditions.The exploratory study illustrated attempts to test this hypothesis, by undertaking an experiment informed by phenomenological and embodied cognition theories. We analysed the spatial unit of the corridor, altered in twenty-one variations. We modified one potentially atmospheric parameter at a time, and collected emotional responses of participants. Subjects interacted with immersive virtual-reality settings. Our findings demonstrate that an experimental approach is applicable to evaluating atmospheric perception and suggest which architectural features seem to interplay with the empathic sensibility of the perceiver (i.e. colours and material patterns) and which ones do not (i.e. lighting qualities).